Pemodelan dan Simulasi Secara Tunak dan Dinamik pada Pengeringan dengan Rotary Dryer - Herry Santoso (Seminar Nasional Teknik Kimia Kejuangan, 2015)
Rotary dryer is one of the dryers that has many uses in chemical, pharmacy, and food industries. The model which represents the actual condition of rotary dryer is needed to make the designing and scaling-up of this dryer easier. The objective of this study is to proposed mathematical model of drying process with rotary dryer in the form of distributed parameter system and then simulate this drying process in its steady state and dynamic condition. The variables that was observed in this model are moisture in the solid feed, moisture in the drying air, temperature of the solid feed, and temperature of the drying air. This non-linear partial differential equations was modified to non-linear ordinary differential equations using finite difference method and then solved using numeric integration technique. The steady state simulation shows that changes in inlet variables have influence to the observed variables on the outlet of rotary dryer with the greatest effect is from the temperature of drying air and the lowest effect is from the temperature of solid feed. Furthermore, the dynamic parameters obatained from dynamic simulation can be used for controlling purpose.